The Impact of Big Data Analytics Capabilities on Competitive Advantage Applied on “Etisalat Egypt” - Omar, Amira (The Arab Journal of Administration, 2020)
The purpose of this study is to investigate how Big Data Analytics is used and perceived to affect a firm’s competitive advantage. The study will focus on the telecommunication sector, due to the high volume of data being used for analysis in this sector; it is always an area of great interest. This paper investigates the role that Big Data Analytics Capabilities play in achieving a competitive advantage in the Egyptian telecommunication sector. Using the Dynamic Capabilities framework, this paper looks at how a firm can gain an advantage from big data. For collecting data, the study adopted the questionnaire method; the study used the questionnaire-based survey method; the study used two questionnaires; one for big data analysis department employees to investigate the independent variable Big Data Analytics capabilities, and the other one for the top and middle managerial levels employees to investigate the dependent variable competitive advantage. The results show that there is a statistically significant impact of “Big Data Analytics Capabilities” on Competitive advantage. Infrastructure flexibility and management capabilities were relatively more important than Personnel Expertise between all the dimensions of Big Data Analytics capabilities. But these differences are small, so all the dimensions should be given the same value in building Big Data Analytics capabilities. Management in the telecommunication sector should take into account that enhancing Big Data capabilities and considering big data as part of their operations can improve their Competitive Advantage and their Performance.